Pemanfaatan Mediapipe Body Pose Estimation dan Dynamic Time Warping untuk Pembelajaran Tari Remo - Effendi, Yusuf; Kristian, Yosi; P.C.S.W, Lukman Zaman; Yutanto, Hariadi (Universitas Merdeka Malang, 2023)
Video can be used as a learning medium for various purposes. In this research, the object of study is the movements of the traditional dance